Description of Sewing Training Program in BLK Sijunjung - Yolanda Nofia Putri; Irmawita Irmawita (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2019)
The study objectives of this study are to describe the learning material, learning methods, learning resources, and learning infrastructure used in the BLK Sijunjung preparation education and training. This type of research is quantitative descriptive. The population of the entire area of the object used as the research sample. The selected sample must represent or represent all participants, namely the inmates who take the skills training to receive 32 people. The data collection technique used was a questionnaire. The data analysis technique used in this study is quantitative descriptive. Research findings 1) Materials provided by general instructors, most of whom are assisted by people who understand and understand the learning materials that are needed by the learning community can provide benefits / assistance to their members. 2) Learning methods used by citizens in skills training have been well implemented so that the assisted citizens can be directly applied / applied in their lives. 3) Learning resources used by tutors for the majority of the training people have been well implemented so that the assisted citizens can be directly applied / applied in their lives. 4) Facilities and infrastructure used by tutors in learning skills training have been carried out and implemented well by the assisted residents, facilities and infrastructures used are quite complete.Keywords: Sewing Skills, BLK